Ceftriaxone, ofloxacin or both in the treatment of enteric fever - Khatri, Rishi; Deo, Rajeeb Kumar; Karki, Binod; Sharma, Arun (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Enteric fever is a common diagnosis in febrile patients admitting to the hospital of Nepal. The treatment of enteric fever, though looks straightforward, in recent times has been complicated by emerging resistance to various antibiotics including fluoroquinolones and cephalosporins.Methods: This was a randomized clinical study done at Shree Birendra Hospital from January 2011 to December 2011. Patients with with high grade fever, headache, relative bradycardia, abdominal pain, diarrhoea  or constipation with normal to low leukocyte count were clinically diagnosed as Enteric fever and were randomized to either ofloxacin or ceftriaxone group, both well accepted first line treatment for enteric fever and observed for at least five days before the addition of the second drug that is ceftriaxone in ofloxacin group and ofloxacin in ceftriaxonegroup and the response to the drug was noted in terms of defervescence of fever.Results: Total 50 patients were enrolled, 25 in each treatment group. After five days, six patients in Ceftriaxone group needed addition of Ofloxacin and two patients in Ofloxacin group needed Ceftriaxone. The average fever defervescence time in Ceftriaxone group was 3.88 days and in Ofloxacin group was 3.04 days. All patients were afebrile by 9 days of antibiotics.Conclusions: Fever defervescence time with Ofloxacin was lesser than ceftriaxone group and need of supplementary antibiotic is lesser in ofloxacine group. So, ofloxacin can be recommended as 1st line drug for enteric fever.Medical Journal of Shree Birendra Hospital; January-June 2013/vol.12/Issue1/37-40DOI: http://dx.doi.org/10.3126/mjsbh.v12i1.9092